Sewage sludge ash as filler in asphalt mastic: Low-temperature towards high-temperature performance - Alireza Azarhoosh; Mehdi Koohmishi; Negar Khakshour Bazkhaneh (Results in Engineering)
The sewage sludge ash (SSA) is characterized as a by-product used in the pavement industry to mitigate the environmental risks, enhance the landfill capacity and conserve the non-renewable resources. This research utilized SSA as a filler substitute in asphalt mastic, and its performance-based properties from low towards high temperatures were evaluated. For this goal, the physical and chemical properties of SSA and rock powder (used as base filler) were determined using BET surface area measurement, X-ray fluorescence, and scanning electron microscopy tests. The performance of base and SSA-modified asphalt mastics in four filler/bitumen weight ratios (0.6, 0.8, 1, and 1.2) was investigated using dynamic shear rheometer, multiple stress creep and recovery, linear amplitude sweep, and bending beam rheometer tests across a wide temperature range. The results indicate that SSA has a higher specific surface area, better bitumen absorption, and lower density compared to the base filler. Additionally, unlike the acidic nature of the base filler, SSA possesses strong basic properties, leading to a stronger chemical bond with bitumen and enhanced resistance to aging, particularly at high temperatures. Moreover, the lower density of SSA escalates the amount of filler per unit volume of the SSA-modified asphalt mastic, leading to the increased stiffness and elasticity. This trend improves resistance to permanent deformation and cracking at medium temperatures, although it has an adverse effect on performance of mastic at low temperatures. Moreover, due to the improved performance of SSA-modified asphalt mastic, this study can contribute to the sustainable development of the pavement industry.